Analysis of Tidal Energy Potential in the Merauke Papua River Waters Indonesia - Sahupala, Peter; Parenden, Daniel (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
The purpose of this study is as a source of information to study the potential of tidal energy at the estuary of the Maro River in the waters of Merauke Regency. This study uses a quantitative method, while the method for determining the location of the study used is the purposive sampling method where the data collection point is right at the end of the estuary of the Maro River because it faces directly onto the Arafura Sea. Tide data for 5 months, namely September 1, 2023 to January 31, 2024 with a pool area of 1,260,000 m2, with the consideration that from September to January there is a change of seasons that can significantly affect the tidal pattern. The tides are measured in two periods, namely the first tidal period starting at 01.00 AM to 12.00 AM and the second tidal period occurs at 01.00 PM to 12.00 PM. From the research data, it was obtained that the highest tides were in January 2024, namely the first-period tidal height difference of 5.333 meters and the energy produced was 5.292 kWh, and the second-period tidal height difference was 5.383 meters the energy produced was 5.349 kWh. The results of this study can encourage diversification of energy sources in Merauke and increase regional energy security as well as provide the data needed for further research and development of renewable energy technology, which can accelerate innovation of new technologies in the Merauke Papua region.